Pemberian H2so4 dan Air Kelapa pada Uji Viabilitas Biji Kopi Arabika (Coffea arabika L.) - Masnur Turnip, Hedty, Mukarlina (Jurnal Protobiont, 2014)
Arabica Coffee is important plant in Indonesia. The coffee seeds can be germinated normally, without special treatment, in 6 8 weeks, special treatment either physically or chemically can faster dormancy of the seeds, so they can germinate in 4 6 weeks after seedling. This research aimed to know the influence of giving H2SO4 and coconut water in speeding seed dormancy which was conducted for 2 mounths from January to March 2013 in the greenhouse of faculty of Mathematics and Natural Science, Tanjungpura University Pontianak. The research methodology used factorial experiment with complete randomized design which consisted of two treatments that are concentration H2SO4 with four levels: control, concentration 15%, 20% and 25%. The second factor was concentration of coconut water with four levels that are conrol, concentration 60%, 80% and 100%, each of these was treated repeatedly, thus 48 unit trials were achieved. The research showed that giving 20% H2SO4 and 100% coconut water can speed seed dormancy with germination percentage 86,66%, germination growth 30,46% and speed of growth 41,65%.